Faster, slower or real time? Perceptual-cognitive skills training with variable video speeds. (July 2016) - Put, Koen; Wagemans, Johan; Pizzera, Alexandra; Williams, A. Mark; Spitz, Jochim; Savelsbergh, Geert J.P.; Helsen, Werner F.
Abstract: Objective: We examined whether a short-term, off-field training intervention using different video speed manipulations (i.e., normal speed, 75%, and 125% of normal speed), enhances the offside decision-making performance of international level assistant referees. Moreover, we explored the optimal sequence of various video speed manipulations during training. Design: All groups were exposed to a pre- and posttest. During acquisition, the assistant referees assessed 60 offside video simulations during three different training sessions. The order of the video speed conditions varied during the training intervention depending on participant group assignment: increasing speed group (n = 33; 75%–100%–125%); decreasing speed group (n = 33; 125%–100%–75%); and arbitrary speed group (n = 30; 100%–75%–125%). Results: First, the decision-making accuracy was higher during the presentation of real time and faster video conditions when compared to the slower video condition. Second, only the decreasing speed group improved their offside decision-making performance from pre- to posttest. Conclusions: We conclude that scheduling a decreasing video speed sequence throughout training is more beneficial to enhance learning than increasing or arbitrary speed conditions. Although it is too premature to replace existing training protocols that typically use constant speed videos, the present study offers evidence to suggest that training interventions for elite performers that decreasing the speed of exposure during the learning process may have some benefits over regular speed presentations. Highlights: Off-field perceptual-cognitive training enhances decision-making performance. The use of realistic and life-like video simulations should be encouraged. Video speed manipulations clearly influence the pick up of relative motion. Immediate feedback is important to cognitively suppress visual illusions.